2020
DOI: 10.3390/ijms21228473
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Fe3O4 Superparamagnetic Nanoparticles, Sodium Butyrate, and Folic Acid for Intracellular Transport

Abstract: Combined treatments which use nanoparticles and drugs could be a synergistic strategy for the treatment of a variety of cancers to overcome drug resistance, low efficacy, and high-dose-induced systemic toxicity. In this study, the effects on human colon adenocarcinoma cells of surface modified Fe3O4 magnetic nanoparticles (MNPs) in combination with sodium butyrate (NaBu), added as a free formulation, were examined demonstrating that the co-delivery produced a cytotoxic effect on malignant cells. Two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Therefore, an important issue for GBM treatment is the development of a suitable carrier to protect and deliver a specific drug such as TMZ. In this regard nanostructured systems such as liposomes, polymeric and functionalized inorganic nanoparticles have shown promising results in the delivery of active drugs to the brain [ 10 , 11 , 12 , 13 ] and, in particular, organic functionalized Fe 3 O 4 nanoparticles have attracted increasing attention [ 14 , 15 ] because of the combination of the magnetic properties and biocompatibility of the iron core with the versatility of the functionalization shells [ 16 , 17 ]. Recently, Metal-Organic Frameworks (MOFs) coordination polymers consisting of metal nodes and polydentate organic linkers organized in open porous structures [ 18 , 19 ] and, among them, MILs (Materials Institute Lavoiser) an MOF subclass constituted by trivalent transition metals and bi- or tri-carboxylic ligands, showed great potentiality for biomedical applications either as pure crystals or as composite materials, because of their biocompatibility and capability of loading molecules in their porous structure [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an important issue for GBM treatment is the development of a suitable carrier to protect and deliver a specific drug such as TMZ. In this regard nanostructured systems such as liposomes, polymeric and functionalized inorganic nanoparticles have shown promising results in the delivery of active drugs to the brain [ 10 , 11 , 12 , 13 ] and, in particular, organic functionalized Fe 3 O 4 nanoparticles have attracted increasing attention [ 14 , 15 ] because of the combination of the magnetic properties and biocompatibility of the iron core with the versatility of the functionalization shells [ 16 , 17 ]. Recently, Metal-Organic Frameworks (MOFs) coordination polymers consisting of metal nodes and polydentate organic linkers organized in open porous structures [ 18 , 19 ] and, among them, MILs (Materials Institute Lavoiser) an MOF subclass constituted by trivalent transition metals and bi- or tri-carboxylic ligands, showed great potentiality for biomedical applications either as pure crystals or as composite materials, because of their biocompatibility and capability of loading molecules in their porous structure [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other multifunctional codelivery systems, like mesoporous silica‐coated gold nanorods (GNRs/mSiO2) loaded with DOX, conjugated with pH‐responsive poly‐histidine (PHIS), and covered with d‐α‐tocopherol polyethylene glycol 1000 succinate (TPGS) was discovered to increase the drug accumulation and promote photothermal conversion in tumor resistant CRC cells and exert better anticancer effects in SW620/Ad300 xenograft mice without observed systemic toxicity compared with other chemotherapy or photothermal therapy alone 126 . Combination use of sodium butyrate and Fe3O4 magnetic nanoparticles (MNPs), coated with folic acid (FA) and polyethylene glycol (PEG) (FA‐PEG@MNPs), could decrease cell viability and increase FA‐PEG@MNPs intracellular uptake in Lovo cells, which indicated that the combined use may exert MDR resistance reversal effect in CRC 127 . Due to the multiple advantages of nanocarriers, recently, more studies are focusing on nanocarriers and trying to find different ways to overcome chemoresistance 128,129 …”
Section: New Drug Delivery Systemmentioning
confidence: 99%
“… 126 Combination use of sodium butyrate and Fe3O4 magnetic nanoparticles (MNPs), coated with folic acid (FA) and polyethylene glycol (PEG) (FA‐PEG@MNPs), could decrease cell viability and increase FA‐PEG@MNPs intracellular uptake in Lovo cells, which indicated that the combined use may exert MDR resistance reversal effect in CRC. 127 Due to the multiple advantages of nanocarriers, recently, more studies are focusing on nanocarriers and trying to find different ways to overcome chemoresistance. 128 , 129 …”
Section: New Drug Delivery Systemmentioning
confidence: 99%
“…Despite the high resolution (3–20 nm), imaging is restricted to the surface of the sample. For this reason, SEM has mostly been used in nanomedical research to characterize the spatial relationships between nanoparticulates and the cell surface with particular reference to the internalization process and cell shape modification [ 25 , 26 , 27 , 28 ] although field emission SEM (using a high energy beam of electrons) has allowed the visualization of nanoparticles also in the endosomal compartment [ 29 ].…”
Section: Introductionmentioning
confidence: 99%